Combination of dextromethorphan and memantine in treating bipolar spectrum disorder: a 12-week double-blind randomized clinical trial - Lee, Sheng-Yu (Int J Bipolar Disord, 2020)
BACKGROUND: The aim of this study is to determine whether adding combination of agents with anti-inflammatory and neurotrophic effects is more efficacious than mood stabilizer alone in improving clinical symptoms, plasma brain-derived neurotrophic factor (BDNF), cytokine levels, and metabolic profiles in patients with bipolar spectrum disorder. METHODS: In a randomized, double-blind, controlled 12-week clinical trial, patients with moderate mood symptoms (HDRS ≥ 18 or YMRS ≥ 14) were recruited. The patients were randomly assigned to a group while still undergoing regular valproate (VPA) treatments: VPA + dextromethorphan (DM) (30 mg/day) + memantine (MM) (5 mg/day) (DM30 + MM5) (n = 66), VPA + DM (30 mg/day) (DM30) (n = 69), VPA + MM (5 mg/day) (MM5) (n = 66), or VPA + Placebo (Placebo) (n = 69). Symptom severity, immunological parameters [plasma tumor necrosis factor (TNF)-α and C-reactive protein (CRP)] and plasma brain-derived neurotrophic factor (BDNF) were regularly examined. Metabolic profiles [cholesterol, triglycerides, glycosylated hemoglobin (HbA1C), fasting serum glucose, body mass index (BMI)] were measured at baseline and at 2, 8, and 12 weeks. RESULTS: Depression scores were significantly (P = 0.03) decreases and BDNF levels significantly (P = 0.04) increased in the DM30 + MM5 group than in the Placebo group. However, neither depressive scores nor BDNF levels were significantly different between the DM30, MM5, and Placebo groups. Changes in certain plasma cytokine and BDNF levels were significantly correlated with metabolic parameters. CONCLUSION: We concluded that add-on DM30 + MM5 was significantly more effective than placebo for clinical symptoms and plasma BDNF levels. Additional studies with larger samples and mechanistic studies are necessary to confirm our findings. Trial registration NCT03039842 (https://register.clinicaltrials.gov/). Trial date was from 1 Jan 2013 to 31 December 2016 in National Cheng Kung University Hospital. Registered 28 February 1 2017-Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03039842?term=NCT03039842&rank=1.